Baseline survey and RCMAS interview with farmers in Libmanan, Camarines Sur for delivering climate information service through RCMAS Climate+ - Baradas, Airene Claire; Castillo, Rowena; Balanza, Jane Girly (International Rice Research Institute, 2024)
The report presents initial findings from a baseline survey and interviews conducted with farmers in Libmanan, Camarines Sur, as part of the CGIAR Research Initiative on Climate Resilience or ClimBeR aimed at enhancing climate resilience in rice farming. The study focuses on the integration of the Rice Crop Manager Advisory Service (RCMAS) and the Agro-climatic Advisory Portal (ACAP) to provide actionable climate information and crop management recommendations to smallholder rice farmers. Key findings reveal that farmers in Libmanan face significant climate risks, including flooding, drought, and saline intrusion, which can severely impact rice yields and livelihoods. The survey involved 355 farmers, highlighting their awareness of climate risks and the need for improved access to timely weather information. Results indicate a strong reliance on traditional media for weather updates, with a substantial portion of farmers expressing interest in receiving SMS alerts about critical farming activities. The report underscores the importance of accurate data collection and communication strategies to enhance farmers' adaptive capacity in the face of climate variability.